Together apart: field notes as artefacts of collaborative ethnography. Issue 1 (2nd January 2020) - Safronov, Petr; Bochaver, Alexandra; Nisskaya, Anastasia; Koroleva, Diana
ABSTRACT: This article is drawn from the authors' first experience as school ethnographers who gathered data on eleven- and twelve-year old children in a Moscow school. The focus is on data processing in ethnographic writing. The paper addresses the challenges of making field notes in a collective consisting of researchers with different professional and personal backgrounds. Based on the theories of digitally mediated communication and the accounts of qualitative research as assemblage it examines how collaboration emerges through joint electronic creation of ethnographic field notes. The notion of artefact stemming from theories of computer-aided communication comprises the nature of field notes as complex objects, documenting both the field and the process of collaborative writing. Examples of artefacts and respective reporting strategies are provided. The authors conclude with a discussion of sequences of their approach for further development of the practices of digitally mediated collaborative writing in ethnography.